Prevention of Intensive Care Unit-Acquired Pneumonia - Klompas, Michael (Seminars in Respiratory and Critical Care Medicine, 2019)
Intensive care unit (ICU) acquired pneumonia is one of the most common and morbid health care-associated infections. Despite decades of work developing and testing prevention strategies, ICU-acquired pneumonia remains stubbornly pervasive. Pneumonia prevention studies are difficult to interpret because all are at risk of bias due to the subjectivity and poor specificity of pneumonia definitions. Interventions associated with improvements in objective outcomes in addition to pneumonia, such as length of stay or mortality, should therefore be prioritized. Avoiding intubation, minimizing sedation, implementing early extubation strategies, and mobilizing patients do appear to improve some of these objective outcomes. Many of our other assumptions about how best to prevent ICU-acquired pneumonia, however, have recently been challenged. Elevating the head of the bed is supported by very little randomized trial data. Early reports suggested that subglottic secretion drainage may decrease time to extubation and ICU length of stay, but more recent analyses refute these findings. Novel endotracheal tube cuff designs do not clearly lower pneumonia rates. A large randomized trial of selective digestive decontamination in ICUs with high baseline rates of antimicrobial resistance did not identify any benefit. Oral care with chlorhexidine may increase mortality risk and stress ulcer prophylaxis may facilitate pneumonia. Early data on probiotics suggest a possible effect but there is no clear signal yet that they shorten duration of mechanical ventilation or lower mortality. Ventilator bundles on balance do appear to be beneficial but it is not clear which components are most important nor how best to implement them. This article will review recent studies that have challenged, refined, or complicated our understanding of how best to prevent ICU-acquired pneumonia.
Keywords: ventilator-associated pneumonia; ICU-acquired pneumonia; spontaneous breathing trials; oral care with chlorhexidine; subglottic secretion drainage; stress ulcer prophylaxis; endotracheal tube cuff design; selective digestive decontamination; probiotics